TV 1.9: A experiência das webTVs universitárias (Significação: Journal of Audiovisual Culture, 2011)
The experience of image culture and convergence era effects on every field of social life, reconfigures the means and its mediations and provokes aesthetics and contents innovations. The webTVs are born as singular environments, characterized by a new way to see and make television. This work points possibilities of use of universities’ webTVs as relevant environments to the vocational training, once they are constituted, potentially, by spaces of experimentation of audiovisual language and multimedia resources and socialization. This article presents results of a study about four universities’ webTVs from Rio de Janeiro city.